2017
DOI: 10.1159/000478761
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of the Ethyl-Acetate Fraction of Trichilia catigua in Streptozo-tocin-Induced Type 1 Diabetic Rats

Abstract: Background/Aims: Trichilia catigua A. Juss., known as "catuaba" in Brazil, has been popularly used as a tonic for fatigue, impotence and memory deficits. Previously, our group demonstrated that the ethyl-acetate fraction (EAF) of T. catigua has antioxidant and anti-inflammatory effects. The present study evaluated the anti-diabetic activity of EAF in type 1 diabetic rats. Methods: Male Wistar rats were divided into four groups (N: non-diabetic group, D: type 1 diabetic group, NC: non-diabetic + EAF group and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Extracts rich in polyphenol compounds from several plants have been reported to be effective against cell damage mediated by reactive oxygen species by increasing antioxidant defenses and reducing hyperglycemia [ 35 ]. Fractions obtained using the ethyl acetate solvent have a high concentration of polyphenols, as has been obtained from Trichilia catigua [ 36 ], grape skin [ 37 ], and stevia leaves [ 22 , 38 ]. In addition, insulin-producing effects of polyphenols in chronic treatment in vivo , in pancreatic islet culture, and in insulin-producing cells [ 39 , 40 ] have been reported, but direct effects on isolated islets, such as those shown in the current work with a fraction of stevia, have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts rich in polyphenol compounds from several plants have been reported to be effective against cell damage mediated by reactive oxygen species by increasing antioxidant defenses and reducing hyperglycemia [ 35 ]. Fractions obtained using the ethyl acetate solvent have a high concentration of polyphenols, as has been obtained from Trichilia catigua [ 36 ], grape skin [ 37 ], and stevia leaves [ 22 , 38 ]. In addition, insulin-producing effects of polyphenols in chronic treatment in vivo , in pancreatic islet culture, and in insulin-producing cells [ 39 , 40 ] have been reported, but direct effects on isolated islets, such as those shown in the current work with a fraction of stevia, have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of islet area were performed by Image-Pro Plus using specific area measurement tools. The relative beta-cell mass per pancreas area, was determined by point counting morphometry on each pancreas section immunostained for insulin according previous descriptions ( Xu et al, 1999 ; Rafacho et al, 2009 ; Malta et al, 2016 ; Gomes et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the evaluation of histopathological studies demonstrated that activate AMPK signaling pathway attenuate the kidney tissue damage that is caused by STZ-diabetes. STZ-induced type 1 diabetic rats are associated with severe decrease of body weight caused by hyperglycemia, loss of tissue proteins (14), muscular tissue and adipose tissue (15). Additionally, the increase in the levels of serum uric acid and creatinine (16) and the decrease in the levels of serum albumin and total protein (17) have been associated with diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%